Protecting Human Dignity in the Sunnah (Islamic Sciences Journal, 2023)
Human dignity has a high position in the list of major Islamic values. In Islam no harm, and no justification or interpretation that lead to an underestimation of the dignity of a person, regardless of his religion and belief, is accepted.In the scientific scene, two contradictory sects have appeared in their understanding of the value of human dignity in Islamic law: The first sect denies the Islamic Sharia sufficient and complete care for human dignity, and the majority of this group is non-Muslims of different religions and atheistic sects, who limit dignity to specific aspects - each according to his own sect They ignore the many manifestations of agreement between Islam and their sects, which they embrace.The second sect belongs to Islam - from the doctrines and currents that are predominantly exaggerated in religion - but it refuses to limit dignity by merely describing humanity.In this research, I prove the error and extremism of these two sects in understanding the reality of human dignity in Islam and in the Sunnah of the Prophet Mohammed (May Allah Prayers and Peace be upon him) in particular.
Keywords: Dignity, aspects of protection, people with needs, setting standards, the vulnerable segment .